2010
DOI: 10.1016/j.jare.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric methods for the simultaneous determination of binary mixture of metronidazole and diloxanide furoate without prior separation

Abstract: Ratio subtraction and isosbestic point methods are two innovative spectrophotometric methods for determining the concentrations of metronidazole (I) and diloxanide furoate (II) in a mixture. Metronidazole was determined by direct spectrophotometric method at k max 314.0 nm in the presence of diloxanide furoate in the range of 4-24 lg ml À1 with a mean recovery percentage of 99.83 ± 1.41. Two spectrophotometric methods were developed for the spectral resolution of diloxanide furoate when present in mixture with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…The two methods gave more or less concordant results with respect to their precision (F-test) and accuracy (t-test) where the calculated values did not exceed the theoretical values for either one of the three drugs. On the other hand, the proposed HPLC-DAD method can be considered superior to the previously reported method [7] because it is more sensitive and selective. The proposed method provides lower values of LOD and LOQ, for the three drugs than in reported method.…”
Section: Application To Commercial Tabletsmentioning
confidence: 83%
See 3 more Smart Citations
“…The two methods gave more or less concordant results with respect to their precision (F-test) and accuracy (t-test) where the calculated values did not exceed the theoretical values for either one of the three drugs. On the other hand, the proposed HPLC-DAD method can be considered superior to the previously reported method [7] because it is more sensitive and selective. The proposed method provides lower values of LOD and LOQ, for the three drugs than in reported method.…”
Section: Application To Commercial Tabletsmentioning
confidence: 83%
“…The results of analysis of the commercial tablets and the recovery study (standard addition method) of drugs (Table VI) suggested that there is no interference from any excipients, which are normally present in tablets. In addition, the results obtained using the proposed HPLC method were statistically compared with those obtained with the reported TLC method [7]. The two methods gave more or less concordant results with respect to their precision (F-test) and accuracy (t-test) where the calculated values did not exceed the theoretical values for either one of the three drugs.…”
Section: Application To Commercial Tabletsmentioning
confidence: 94%
See 2 more Smart Citations
“…Although the overlapped spectra of Q and HQ make it difficult to quantify these species based on the spectral measurement at a single wavelength, we believe that the problem can be resolved by using novel data acquisition approaches, such as dual-wavelength or tri-wavelength techniques. [13][14][15] In this work, we developed a novel, tri-wavelength spectrophotometric method for the determination of Q and HQ in sample solutions obtained from biochemical conversion processes. The data obtained by the present method were compared with those obtained by HPLC.…”
Section: Introductionmentioning
confidence: 99%